Balancing Teaching, Research, and Service responsibilities: Challenges and Strategies for Academic Staff - ADEGOKE, Alfred Akinbo (Ilorin Journal of Education, 2025)
Academic staff in Nigerian universities face significant challenges in balancing the tripartite responsibilities of teaching, research, and service. This paper critically examines the multidimensional pressures associated with these roles, especially within the context of underfunded public universities, increasing student populations, inadequate infrastructure, and the pervasive “publish or perish” culture. The study highlights how institutional expectations, performance evaluation metrics, and resource allocation can create tensions that compromise teaching quality, researcher integrity, and personal well-being. It also explores the impact of journal proliferation and indexing complexities on academic publication. Drawing on practical strategies such as time auditing, SMART goal setting, prioritization frameworks, and integrated role management, the paper proposes a sustainable model for academic productivity and self-care. It underscores the importance of institutional support, technological tools, boundary setting, and proactive stress management. Concluding that perfect balance may be elusive, the study advocates for continuous reflection, flexible scheduling, and the celebration of incremental successes as essential strategies for academic resilience and fulfillment.